Pengaruh Partisipasi Penyusunan Anggaran Terhadap Kinerja Aparat Pemerintah Daerah Kab. Rokan Hilir Dengan Gaya Kepemimpinan, Desentralisasi dan Komitmen Organisasi Sebagai Variabel Moderating (Studi Empiris Pada SKPD Kab. Rokan Hilir) - Riza Lestari; Vince Ratnawati; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study to test empirically to related effect of budgetparticipation on the performance of local government officials with leadership style, decentralization and organizational commitment as a moderating variable in the district Kab. Rokan Hilir. Data collected by distributing questionnaires to the respondents. Population used in this study were all echelon II, III and IV in 15 work units (SKPD) in Kab. Rokan Hilir. The analytical method used is multiple regression wearing T-test using SPSS 17.00. The result of this study it is conclouded that in partial budget participation has an influence on the performance of local government officials. The result of the second test for inteeraction and leadership style also suggest that the effect on the relationship between budgetary participation and performance local government. And for the result of the decentralization variable interactions are also significant effect on the relationship of participation and performance of local government officials. Interaction and ttest result, which showed that the four organizational commitment can not moderate the relationship between budget participation on the performance of local government officials.Keywords : Budget Participation, Leadership Style, Decentralization, andOrganizational Commitment